A randomized, fixed-dose, dose–response study of ropinirole prolonged release in advanced Parkinson's disease. (February 2017) - Zesiewicz, Theresa A; Chriscoe, Stephen; Jimenez, Theresa; Upward, James; Davy, Maria; VanMeter, Susan
Aim: This Phase IV, double-blind, randomized, parallel-group study characterized the dose-response and tolerability of fixed doses of ropinirole prolonged release (PR) in subjects with advanced Parkinson's disease.Patients & methods: Subjects receiving concomitantl -dopa received once-daily ropinirole PR 4, 8, 12, 16 or 24 mg, or placebo, up-titrated for 13 weeks, maintained for 4 weeks.Results: At maintenance period week 4, ropinirole PR significantly reduced total awake 'Off-time' (16 mg; p = 0.027); increased absolute awake time spent 'On' without troublesome dyskinesia from baseline versus placebo (8 mg; p = 0.036); improved Unified Parkinson's Disease Rating Scale motor scores versus placebo (all doses; p = 0.005–0.016). Incidence of adverse events was similar between treatment groups; no dose-related trends were observed.Conclusion: Ropinirole PR (16 mg) reduced 'Off-time' with 8 mg the likely lowest maximally effective dose, and the safety profile was consistent with previous studies.